Rethinking library neutrality to face disinformation: some proposals from professional ethics - Macías-Vicente, Luis-Miguel (Revista de Investigación sobre Bibliotecas, Educación y Sociedad, 2024)
Disinformation, a complex and problematic phenomenon, is not alien to libraries. Librarians are experts in the are experts in the search, retrieval, processing and dissemination of information and, as such, have the capacity to deal with this challenge. In our profession, codes of ethics are a fundamental tool to facilitate our professional performance. Therefore, the main objective of this article is to analyse the codes of IFLA, ALA, CILIP, ALIA, SEDIC, ABF and BAD, APDIS and INCITE, focusing on those aspects that have a more direct relationship with disinformation: access to information, neutrality and freedom of expression and opinion, among others. As a result of this analysis, the concept of neutrality in the library field is discussed and an update of the codes of ethics of the different associations and organisations is argued for to allow librarians to act more directly in the face of disinformation.